Network Pharmacology and Molecular Docking on the Molecular Mechanism of Luo-hua-zi-zhu (LHZZ) Granule in the Prevention and Treatment of Bowel Precancerous Lesions - Guo, Cui; Kang, Xingdong; Cao, Fang; Yang, Jian; Xu, Yimin; Liu, Xiaoqiang; Li, Yuan; Ma, Xiumei; Fu, Xiaoling (Frontiers in Pharmacology, 2021)
Objective: To explore the active ingredients and potential mechanisms of Luohuazizhu (LHZZ) granule in prevention and treatment of colorectal adenoma using network pharmacology and molecular docking analysis. Method: The main chemical constituents of LHZZ granule were identified by mass spectrometry, and the targets of the compound were screened by the Pubchem and SwissTargetPrediction database. The disease targets were searched in the GeneCards, DisGeNET, Drugbank and OMIM databases with the key words of "intestinal adenoma and precancerous lesions". The name of the target was corrected by Uniprot database, and the chemical components of LHZZ granule intersected with the disease target were found. The traditional Chinese medicine-compound-target network was constructed by Cytoscape3.7.2 software for visualization. gene ontology (GO) functional enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were carried out through DAVID database, the mechanism of action of intersection target was predicted, and column chart and bubble chart were drawn for visualization. The AutoDockvina was used for molecular docking to predict the key targets of colorectal adenomas. Results: The traditional Chinese medicine-compound-target network includes 1 Chinese medicine, 24 compounds and 381 corresponding targets. The key targets involve TP53, CASP3, AKT1, HRAS, et al. The GO functional enrichment analysis yielded 150 entries, KEGG pathway enrichment analysis screened 71 signaling pathways. The results of molecular docking showed that the active component of LHZZ granule had good binding activity to the core target protein of colorectal adenoma. CONCLUSION: The LHZZ granule can be used to prevent and treat intestinal adenoma through multiple components, multiple targets and multiple pathways. Its molecular mechanism is related to targets such as TP53, CASP3, AKT1, and HRAS, and involves in pathways in cancer, PI3K- Akt signaling pathway, p53 signaling pathway, and cell apoptosis. This study will lay a foundation for subsequent multi-target drug development and molecular clinical research.